The Effet Of Platelet Rich Fibrin on Osseous Regeneration After Jaw Cysts Enucleation (Journal of Hama University, 2021)
The platelet rich fibrin (PRF) is second generation platelet concentrate that has been widely used and researched for stimulation and acceleration of soft tissue and osseous healing. Its continuous delivery of growth factors and proteins mimic the need of physiological wound healing and regenerative tissue processes.The aim of this study was to evaluate the efficacy of PRF in osseous regeneration after enucleation of jaw cystic lesions.10 cases of cystic lesions were treated using PRF after cystic enucleation. Follow-up radiographs (orthopantomogram) were taken postoperatively and after  6  months . A method of measurements to assess the percentage of reduction of the bone cavities was used to objectify the results.The subsequent follow-up examinations revealed progressive, predictable, and significant radiographic osseous regeneration. The use of PRF in management of cystic lesions seems to be a novel therapeutic approach promoting faster osseous regeneration within 6 months postoperatively. however further study is required with larger sample size and with a control group.